O sferze sacrum w Pamiątce po dobrej matce Klementyny z Tańskich Hoffmanowej - Kozaryn, Dorota (Slavia Occidentalis, 2014)
This paper discusses linguistics methods for evoking the sacrum in Klementyna Hoffman’s of the Tańskis debut as a novelist, titled Pamiątka po dobrej matce. [Remembrance after a Good Mother]. The conducted analysis proved that in the novel in question, the sacrum had been equated with Christian religiousness.